Effect of a Reactive-Type Flame Retardant on Thermal Stability of Thiol-ene Composites. Issue 2 (1st February 2022) - Bao, Xiaohui; Wu, Fangyi; Wang, Jiangbo
Abstract: A reactive-type flame retardant, polyvinylphenylsilsesquioxane (PVP), was synthesized and incorporated into thiol-ene (TE) to prepare a flame-retardant TE (FRTE) composite. The thermal stability and thermal degradation kinetics of TE and FRTE in nitrogen were studied by thermogravimetric analysis (TGA). The effect of PVP in dynamic measurements of the kinetic parameters of TE degradation, such as apparent activation energy, was also investigated by the Kissinger and Flynn-Wall-Ozawa methods. The results of TGA showed that the addition of PVP improved the thermal stability of TE in nitrogen. The kinetic results indicated that the apparent activation energy for degradation of the FRTE composites was higher than that of neat TE, suggesting that the flame retardant PVP used in this work could promote the formation of char residue to block the heat flow and delay the thermal degradation of the TE matrix.